(untitled) (FAVE Sección Ciencias Veterinarias, 2024)
Thermotolerant Campylobacter (TC) are considered the most common bacterial cause of human gastroenteritis in the world. These bacteria circulate frequently in poultry, which are the main source of infection for humans. The main risk factor is the manipulation of fresh chicken meat for preparation of food at home. Nonetheless, wild birds have been frequently reported infected by CT. In spite of that, to date it is not clear which role they have in the epidemiology of this zoonotic agent. This work reviews the current scientific knowledge on CT in wild birds. Most studies in those animals have been conducted in productive systems, mainly broiler farms, where the main species reported is Campylobacter jejuni. To a lesser extent, there are studies in urban areas and natural settings. The prevalence of CT in wild birds appears to be associated to the taxonomic family, the ecological guild, and geographic distribution of the diverse avian species. The exant literature suggests that wild birds may have the potential of playing a considerable role in CT epidemiology, getting involved in the following, 1) being alternative reservoirs; 2) transporting CT to varying distances; and 3) being compartments in which CT antimicrobial resistance can be maintained and generated.